Pandora's Box in Surrogacy: The Paradox of Legal Altruism and the Threat of Human Trafficking - Gisymar, Najib A.; Noorhidayah, Noorhidayah; Naufal, Naufal; Purnawirawan, Agung Cucu; Suhra, Sarifa (IHSA Institute, 2025)
The practice of surrogacy is now an international debate, colored by the tension between the legal policies that regulate this practice and the potential for exploitation and human trafficking. Some countries, such as Italy, prohibit this practice with severe sanctions, while others, such as India and Thailand, legalize it with certain restrictions, prioritizing the altruistic dimension. This article explores the paradox contained in surrogacy, considering it as a Pandora's box that contains both hope and serious potential risks, especially related to the threat of exploitation and human trafficking. This study adopts a normative legal approach by comparing the regulation of surrogacy in countries that allow and prohibit this practice. The methodology used is a socio-conceptual approach, where data is collected through a review of literature and related international conventions, and analyzed with a teleological interpretation to understand the purpose of the rules and the developing legal phenomena. The research findings show that although surrogacy can offer reproductive solutions, this practice often gives rise to ethical and legal dilemmas that threaten the human rights of both surrogate mothers and the children born. Therefore, it is important to find a middle ground that ensures the protection of all parties involved, both those who support or oppose this practice